Analisis Faktor-faktor yang Mempengaruhi Produktivitas Kerja Karyawan di PT. Multi Terminal Indonesia - Retno Ayu Hastuti; Tri Bodroastuti; Tantri Widiastuti (Jurnal Ilmiah Aset, 2021)
Work productivity is the ability to carry out activities that produce an output or work in accordance with the quality set, but often there are obstacles that cause the company's goals to be less achieved. Every company has a different policy on efficient sourcing. The purpose of this study was to determine and analyze how the effect of knowledge, skills, abilities, attitudes and behavior on work productivity of PT. Multi Terminal Indonesia. The population in this study were 30 employees and the entire population was sampled. The analytical tool used in this research was Multiple Linear Regression Analysis. The results showed that knowledge (X1), skills (X2), abilities (X3), behaviors (X5) had no effect on work productivity. The attitude (X4) had an effect on work productivity. The results of simultaneous hypothesis testing explained that knowledge (X1), skills (X2), abilities (X3), attitudes (X4) and behavior (X5) haved an effect on work productivity. The coefficient of determination of 0.636 means that knowledge, skills, abilities, attitudes and behavior are able to explain work productivity by 63.6%. The remaining 36.4% is explained by other variables not included in this research model.